Komunikasi Interpersonal antara Guru dan Siswa dalam Kegiatan Pembelajaran di SMKN 1 Muara Bungo - Rachmah, Yesi Isnaini; Sarmiati, Sarmiati; Azwar, Azwar (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2024)
This qualitative case study investigates teacher-student interpersonal communication at SMK N 1 Muara Bungo, with a specific focus on its effectiveness in addressing student delinquency. The findings underscore a nurturing environment that cultivates empathy and fosters social cohesion. Teachers demonstrate unwavering dedication, extending their support beyond school hours, which potentially aids in mitigating delinquent behaviors. Notable outcomes include heightened understanding, positive attitude shifts, and observable behavioral improvements among students. However, persistent challenges such as language barriers and the influence of technology hinder educators' efforts in effectively addressing delinquency. The study emphasizes the crucial role of nurturing positive relationships, providing sustained support, and implementing appropriate regulations and supervision to optimize communication strategies. By prioritizing these elements, educators can enhance their ability to create conducive environments that foster effective communication, ultimately contributing to a reduction in delinquency rates and promoting positive student outcomes.